New syllabus primary mathematics workbook 2a (supplementary reading material) - Yee, Dr Foong Pui; Chnag Suo Hui Lim Li Gek Pearlyn Wong Oon Hua (Oxford University Press Karachi, 2022)
It covers essential topics such as numbers, operations, geometry, measurement, and data handling through engaging activities and practical examples. The book emphasizes problem-solving and critical thinking, aiming to foster a positive attitude towards mathematics while providing clear explanations and progressive learning strategies.